Kajian awal variabiliti ionosfera di Parit Raja, Batu Pahat pada bulan September 2004 - Abdullah, Sabirin (2004)
The ionosphere study is carried out in Malaysia for September 2004 using ionosphere sounder. The main purpose of the study is to determine the parameters used to search the variability of the ionospheric region in Malaysia. Observations and analysis using gathered data from the colleting and storing data in the sounder system. The result base on the ordinary wave critical frequency for stratification in the F region, foF2, the virtual height for ordinary wave critical frequency or foF2, and the ordinary wave critical frequency from the lowest thick layer of E region. The 24 hours data from 1 September to 30 September have been done to search the median, lower decile and upper decile frequency. The changes of the frequency is dependent on the solar activity in the morning. The highest critical frequency is 6.8 to 12 MHz and decreasing value due to late evening and night time at 7 MHz. The virtual height for this frequency are 200 to 480 km. The E-region frequency is from 2.2 to 9.1 MHz.